(untitled) (e-Journal of Linguistics, 2019)
Speaking as the most demanding skill to be mastered in the ESL/EFL teaching context. This is caused by the prime priority of students who want to study English in order to be able to use English for communicative purposes. Knowledge of language functions has a vital role in supporting a speaker to be more involved in the real interaction. The aims of this study are to identify and analyze the kinds of language functions and how their use in the speaking for academic purposes course. This study was conducted at Universitas Katolik Indonesia Santu Paulus Ruteng, Flores. The data were taken from 33 English department students who were doing the English speaking exercises at the speaking for academic purposes course. The data were collected through observation, field note and recording during eight meetings on October- November 2018 and only language functions utterances of those respondents were analyzed. The recorded utterances are expected to be representative of the whole the language functions. Utterances produced by respondents were recorded precisely by the researchers. The result showed that there are five types of language functions found, namely interactive function, informative function, manipulative function, motivative function and directive functions. Those functions are reciprocal. Speaking practitioners are suggested to provide the knowledge of language functions in the speaking learning process.